Aucubin Exerts Anticancer Activity in Breast Cancer and Regulates Intestinal Microbiota. (16th May 2022) - Shao, Min; Kuang, Ziyun; Wang, Wenlin; Li, Shengnan; Li, Guizhen; Song, Yu; Li, Haitao; Cui, Guozhen; Zhou, Hefeng
Abstract : Aucubin, a natural compound isolated from herbal medicine, has been reported to possess multiple beneficial properties. In this study, we aimed to verify the anticancer effect of aucubin on breast cancer and investigate the effect of cancer on the intestinal flora and whether aucubin has a therapeutic effect on intestinal problems caused by cancer. We established the breast cancer model with mouse 4T1 cell line and BALB/c mice. Aucubin was given once a day by gavage for 14 days. The results showed that aucubin suppress the growth of tumor in vivo by inducing tumor cell apoptosis. The tumor suppression rate of aucubin could reach 51.31 ± 4.07%. Organ histopathology was evaluated by tissue staining, which demonstrated that aucubin could alleviate the organ inflammatory damage caused by breast cancer without visible side effects. Moreover, aucubin could increase the expression of colonic tight junction protein occluding and adjust the gut microbiome to normal level according to 16S rDNA high-throughput sequencing. Herein, our results provide evidence for developing aucubin as an alternative and safe therapeutic for breast cancer treatment.